Acute resistance exercise reduces increased gene expression in muscle atrophy of ovariectomised arthritic rats - Jr, Roberto Furlanetto; Souza, Aletéia de Paula; Oliveira, Anselmo Alves de; Nunes, Paulo Ricardo Prado; Michelin, Márcia Antoniazi; Chica, Javier Emilio Lazo; Murta, Eddie Fernando Candido; Orsatti, Fábio Lera (Menopause Review/Przegląd Menopauzalny, 2016)
Objective: We studied the effect of resistance exercise (RE) on mRNA levels of atrogin-1, MuRF-1, and myostatin in the gastrocnemius muscle of arthritic rats after loss of ovarian function (LOF). Material and methods : Thirty female Wistar rats (nine weeks old, 195.3 ±17.4 grams) were randomly allocated into five groups: control group (CT-Sham; n = 6); group with rheumatoid arthritis (RA; n = 6); group with rheumatoid arthritis subjected to RE (RAEX; n = 6); ovariectomy group with rheumatoid arthritis (RAOV; n = 6); and an ovariectomy group with rheumatoid arthritis subjected to RE (RAOVEX; n = 6). After 15 days of intra-articular injections with Met-BSA the animals were subjected to RE and six hours after workout were euthanised. Results : The rheumatoid arthritis provoked reduction in the cross-sectional area (CSA) of muscle fibres, but the CSA was lower in the RAOV when compared to the RA groups. Skeletal muscle atrogin-1 mRNA level was increased in arthritic rats (RA and RAOV), but the atrogin-1 level was higher in RAOV group when compared to other arthritic groups. The Muscle MuRF-1 mRNA level was also increased in the RAOV group. The increased atrogin-1 and MuRF-1 mRNA levels were lower in the RAOVEX group than in the RAOV group. The myostatin mRNA level was similar in all groups, except for the RAOVEX group, in which it was lower than the other groups. Conclusions : LOF results in increased loss of skeletal muscle-related ubiquitin ligases (atrogin-1 and MuRF-1). However, the RE reduces the atrogin-1, MuRF-1, and myostatin mRNA levels in muscle of arthritic rats affected by LOF.